2016
DOI: 10.1111/jbg.12219
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression in Zebu cattle traits

Abstract: The productivity of herds may be negatively affected by inbreeding depression, and it is important to know how intense is this effect on the livestock performance. We performed a comprehensive analysis involving five Zebu breeds reared in Brazil to estimate inbreeding depression in productive and reproductive traits. Inbreeding depression was estimated for 13 traits by including the individual inbreeding rate as a linear covariate in the standard genetic evaluation models. For all breeds and for almost all tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
3
26
2
1
Order By: Relevance
“…The inbreed coefficient values considering only inbred animals were also similar, ranging from 12.75 to 13.02%. These results may cause important losses, because the animal's performance may be compromised by increasing inbreeding (Santana Jr. et al, 2010;Pereira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The inbreed coefficient values considering only inbred animals were also similar, ranging from 12.75 to 13.02%. These results may cause important losses, because the animal's performance may be compromised by increasing inbreeding (Santana Jr. et al, 2010;Pereira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Baes et al 14 and Marras et al 18 studied the interval from first insemination to calving, which is defined as the IFL plus the gestation length. However, Pereira et al 19 showed that increased inbreeding did not affect the gestation length, suggesting why the lengthening in first insemination to calving can www.nature.com/scientificreports www.nature.com/scientificreports/ be compared with that in IFL caused by the unfavourable genotype. Marras et al 18 found an effect of around 14 days for heifers and 23 days for first-parity cows.…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding can be defined as the probability of an individual receiving, at a given locus, the same ancestral-allele from both parents (Wright, 1922). Several studies have reported the negative effects of inbreeding in sheep (e.g., Drobik and Martyniuk, 2016;Gholizadeh and Ghafouri-Kesbi, 2016), goats (Deroide et al, 2016;Mahmoudi et al, 2018), and cattle (Smith et al, 2010;Pereira et al, 2016;Reverter et al, 2017). Therefore, monitoring inbreeding is important to avoid inbreeding depression.…”
Section: Inbreedingmentioning
confidence: 99%